Advances in Pacific Basin Business, Economics and Finance - Lee, Cheng-Few (Rutgers University, USA); Yu, Min-Teh (Providence University, Taiwan) (Advances in Pacific Basin Business, Economics and Finance, 2025)
Advances in Pacific Basin Business, Economics and Finance (APBBEF) is a peer-reviewed journal published by Emerald Publishing and is designed to focus on interdisciplinary research in finance, economics, and management among Pacific Rim countries. All articles published are peer-reviewed and recommended by one editorial board member. Topics of interest include, but are not limited to, the following:1. Policy and management on financial markets and financial institutions;2. Options, futures, and other derivatives markets;3. Corporate finance and investment decisions;4. Insurance and risk management;5. Accounting, auditing, and taxation;6. Artificial intelligence and new technology in finance;7. ESG and sustainability;8. Income, employment, and education;9. Monetary and foreign exchange policy;10. Other economic policies among the Pacific Rim countries.